Financial Planning Is Influenced By Lifestyle, Financial Literacy And Accounting Mental (Case Study Of Accounting Students In Bengkulu City) - Merita Tri Resky; Rini Indriani; Novita Sari (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This study aims to determine the influence of lifestyle, financial literacy, and accounting mentality on the financial planning of accounting students in Bengkulu City. This study uses a quantitative approach with a survey method and primary data collected through an online questionnaire using Google Forms and barcode scans distributed directly and via the WhatsApp application. The population in this study were active undergraduate and graduate students in accounting study programs at various universities in Bengkulu City in the 2022/2024 academic year. The research sample consisted of 80 respondents determined by purposive sampling based on certain criteria, namely active undergraduate and graduate students in the 2022/2024 academic year, who had taken Accounting and Investment Management courses, and had income other than from their parents. The data analysis techniques used included descriptive statistical tests, data quality tests, classical assumption tests, multiple regression analysis, determination coefficients, and t-tests, with the help of SPSS version 27 for IoS software. The results of the study indicate that the variables of Lifestyle and Financial Literacy have no effect on Financial Planning, while Accounting Mentality has a positive effect on Financial Planning